Phytochemical Screening and Antioxidant Activity of Clerodendrum disparifolium Leaves - ฉัตรธีระนันท์, ศรินรัตน์; สบายใจ, วรางคณา; นิยมไทย, สิริมาส (KKU Science Journal, 2013)
Phytochemical screening of the ethyl acetate and 95% ethanolic extracts from the dried leaves of C. disparifolium revealed the presence of bioactive substances such as flavonoids and alkaloids. The anthraquinones, terpenoids, tannins, saponins and cardiac glycosides were also tested but not found. The antioxidant activity and total phenolic content were evaluated according to DPPH assay and Folin-Ciocalteu method, respectively. The results showed that ethyl acetate and ethanolic extracts had antioxidant activities calculated in IC50, 4.46±0.04, 4.03±0.14 mg/mL, respectively. The total phenolics content of the ethyl acetate extract was 258.84±3.84 mg GAE/g extract whereas the ethanolic extract was 289.49±1.32 mg GAE/g extract. The correlation between antioxidant activity and total phenolics content was observed with correlation coefficient 0.8191.